The Balloonatic - Cline, Edward 1892-1961; Keaton, Buster 1895-1966; Lessley, Elgin 1883-1944; Haver, Phyllis 1899-1960; London, Babe 1901-1980 (EurekaVideo, 2001)
A hapless amusement park attendant finds his runaway balloon ride has left him in a strange predicament. [imdb.de]
Original: USA 1923
Bildformat: aspect ratio 4:3
Keywords: Film; DVD-Video